The Role Of Parents In Improving Literacy Skills Of Elementary School Students In Early Grades Through A Home-Based Literacy Program (A Case Study On Early Grades In Bantul Regency, Yogyakarta) - Endi Rochaendi; Akhsanul Fuadi; Indah Perdana Sari; Yusinta Dwi Ariyani; Dyahsih Alin Sholihah; Siti Asiatun; Nur Kholik (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study employs a case study method with a qualitative approach to understand the home-based literacy program and its impact on early-grade students' literacy. Data were collected through interviews, observations, audio recordings, and written documents from principals, parents, and teachers. Data analysis was conducted using thematic techniques, triangulation, and interpretation to explain the role of parents in enhancing students' literacy skills. The research findings indicate that parental involvement is crucial in supporting elementary school students' literacy abilities. Good literacy skills at an early age form a critical foundation for future academic success and cognitive development. The home-based literacy program is an effective approach that requires active parental participation. Creating a rich reading environment, establishing daily reading routines, and integrating literacy into everyday activities can increase children's interest and reading skills. Support from technology, social, and emotional backing, along with collaboration with schools and communities, ensures the improvement of students' literacy and educational quality. The home-based literacy program enhances the success of the learning process and the quality of education by actively involving parents in supporting children's literacy.